Quality control by flow cytometry and media fill test of autologous leukocytes marked with 99mTc-HMPAO to be used for the “in vivo” infection diagnosis - Paroni, Rita; Maioli, Claudio; Marchetti, Giulia; Crosta, Giacomo; Vismara, Giuseppina; Nan, Mahrail; Sadikovic, Aldijana; Goggi, Ilaria; Petroni, Anna; Capozza, Antonella (Acta Biomedica Atenei Parmensis, 2025)
Background and aim: Infectious processes can be diagnosed using 99mTc-HMPAO labeled autologous leukocytes. The prepared autologous leukocytes once separated and labeled should be neither activated nor apoptotic, so capable of reaching the infectious site. Commonly only cell vitality by Trypan Blue test is assessed. For a comprehensive quality control analysis of the leukocyte preparation, the use of the cytofluorimetry technique is advisable, and, in addition, the sterility of the whole process should be assessed. This work aimed at checking the quality of the labeled leukocytes routinely prepared and used for diagnosis in our Unit, using optimized cytofluorimetry analysis with specific cell biomarkers. Methods: Leukocytes from 11 patients were separated, labeled, and controlled by cytofluorimeter after labeling with Annexin V, CD 66, CD 64, CD 45, and 7AAD markers of activation, apoptosis, and lysis, respectively. In addition, the sterility of the entire process was assessed using “Media Fill test”. Results: In all the patients tested, about 80% of the cells remained inactivated and suitable for diagnostic use “in vivo.” The small portion of activated leukocytes did not affect the preparation’s diagnostic use. The Media fill test demonstrated sterility throughout all the process steps. Conclusions: Cytofluorimetry was demonstrated to be an accurate and useful method for assessing the viability of labeled autologous leukocytes. This could be used both in the process validation phase and when the scintigraphy analysis provides ambiguous results. The Media fill used in the clinical context can be run during the validation and re-validation phases of the entire process.